Ausbau von Wärmenetzen vs. energetische Sanierung? – Umgang mit konkurrierenden Strategien zur Umsetzung der „Wärmewende“ auf kommunaler Ebene - Schubert, Susanne (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Strategies to integrate renewable energies into urban heat supply are often based on the installation and development of district heating grids. At the same time the energetic transformation of the building stock to reduce energy demand has been described as a competing strategy to grid-based systems, due to the characteristics of heating grids which generally are dependent on a comparatively high energy demand. Against this background the article asks, how far heating grids and energetic renovation are incompatible and therefore competing strategies to reach the thermal energy transformation. Based on results from case studies the article lines out, how these strategies are implemented at the municipal level. It is shown that competition as well as adaption and synergies are ways to cope with the existence of the two strategies.